2013
DOI: 10.5586/am.2009.009
|View full text |Cite
|
Sign up to set email alerts
|

Yeast-like fungi isolated from indoor air in school buildings and the surrounding outdoor air

Abstract: A total of 111 isolates of yeast-like fungi and yeasts belonging to 40 species of 19 genera were identified in indoor air and outdoor air. Only one species, Kluyveromyces marxianus, was recorded in both types of air and seasons (spring and autumn). Kluyveromyces lactis and Yarrowia lipolytica, a species having the greatest symbiotic abilities, dominated in indoor air and outdoor air, respectively. Intensely used rooms, especially those with limited access of air, have the broadest range of species of yeast-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…with frequencies of 24.16, 12.96, 12.8, 8.29, and 4.96%, respectively. Similar results were obtained by [50][51][52][53]. Consistently, Al-Suwaine et al [54] mentioned that Aspergillus and Cladosporium spp.…”
Section: Air-conditioning Systems and Moldsupporting
confidence: 89%
“…with frequencies of 24.16, 12.96, 12.8, 8.29, and 4.96%, respectively. Similar results were obtained by [50][51][52][53]. Consistently, Al-Suwaine et al [54] mentioned that Aspergillus and Cladosporium spp.…”
Section: Air-conditioning Systems and Moldsupporting
confidence: 89%
“…As they can produce toxins (e.g. candotoxins), the species can cause mycotoxycoses and increase microorganism sensitivity to some bacterial infections (Ejdys et al, 2009). On the other hand, in outdoor air the most frequent species were moulds Aspergillus flavus and Fusarium oxysporum.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi inhabit a wide range of Earth's environments, including air (Ejdys et al ., ), terrestrial (Säle et al ., ) and marine ecosystems (Soumya et al ., ), and play important roles in biogeochemical cycles (Gadd, ). It has been reported that the global fungal community consists of at least 1.5 million different species; however, only ∼5% of the total species have been described to date, in which Ascomycota and Basidiomycota account for ∼75% and ∼37%, respectively (Deacon, ).…”
Section: Introductionmentioning
confidence: 99%